Online dispute resolution: quo vadis, Europe? - Strikaitė, Goda (Vilnius University Open Series, 2020)
This article discusses potential issues of current European Union regulations in regard to the online dispute resolution, together with potential reasons for low popularity of this way of resolving disputes. The author analyses Her Majesty’s Courts and Tribunals Service (HMCTS) reform programme in England and Wales and compares the online dispute resolution systems as integral parts of courts to the ones functioning independently in the private sector. The article examines the potential for new legal framework promoting the development of online dispute resolution systems in either the private or public sector or in both of them.